ELEMEN VISUAL DALAM PERANCANGAN BRAND IDENTITY YUMAKA - Sulthan Hafiz, Muhammad; Hapsari, Wuri (INSIDE : Jurnal Desain Interior, 2025)
This project designs a brand identity optimization strategy for Yumaka company. This strategy includes visual elements such as logo, color, typography, and design, designed to create a strong and consistent brand identity. The research was conducted through a qualitative approach to understand the needs of the dynamic industry and provide practical solutions in the form of managerial strategies. The purpose of this study aims to explore the role of Brand Identity in the context of the event organizer industry and branding communication, with a focus on Yumaka company. This study aims to identify key elements of brand identity that can strengthen corporate identity and build a consistent and effective communication strategy. The novelty of this study lies in the comprehensive approach to branding communication in the event organizer sector, which often requires high flexibility. This study not only analyzes the visual elements of brand identity, but also integrates theoretical and practical aspects to help companies achieve competitive advantage. In addition, the focus on business sustainability through consistent identity is an important contribution to creating relevance in a highly competitive industry. The methodological approach used is Design Thinking, which consists of five main stages: Empathize, Define, Ideate, Prototype, and Test. Through this method, Yumaka is expected to produce a strong, consistent, and relevant brand identity. This new identity will not only strengthen Yumaka's position in the event organizer industry, but also increase its appeal in the eyes of clients and event audiences. The brand identity strategy for Yumaka has succeeded in achieving its goal of creating a strong, consistent, and attractive visual identity for clients and event audiences. This new identity not only strengthens Yumaka's image as a professional event organizer, but also conveys the company's values ​​in an easy-to-understand way. With a relevant design, following the latest visual trends, and an integrated communication strategy, Yumaka is able to attract the attention of the audience, increase client trust, and strengthen its position in the event organizer industry.